Piano concerto No. 1: in D minor, Op. 15 - Brahms, Johannes. 1833-1897 (Dover miniature scores, 2004)
The young Brahms spent five years struggling to perfect his first piano concerto, a mighty work that, despide a disastrous premiere in 1859, is now considered one of the great monuments of the concerto repertoire.